Packaging for a greener tomorrow: A structural equation model of consumer intentions to purchase environmentally friendly packaged foods in Germany - Pia Drechsel; Alexander H. Kracklauer; Klaus Menrad; Thomas Decker (Cleaner and Responsible Consumption)
The intensive use of plastics, especially single-use packaging, in the food industry significantly impacts the environment. Reducing conventional food packaging is, therefore, a global challenge. While consumers drive market acceptance, it is essential to better understand their decision-making processes. Despite numerous studies, gaps remain in comprehending how consumers form preferences and behavioral intentions regarding sustainable food packaging, particularly concerning their affective and cognitive appraisals. This field study investigated 492 participants directly at the point of sale in four supermarkets across Germany, ensuring that participants were actively engaged in food-purchasing decisions, with their attention already focused on grocery shopping. The study reveals the multifarious factors influencing consumers' preferences and behavioral intentions toward environmentally friendly food packaging alternatives. By applying a structural equation model, it becomes evident that consumer choices are predominantly driven by preferences and emotions rather than knowledge and rational considerations. Environmental concerns also strongly influence consumer awareness and preferences; however, other factors have a greater impact on their behavioral intentions. Our study's distinct approach provides valuable insights into consumer decision-making and highlights that emotionally engaging consumers can strengthen their intrinsic motivation for responsible plastic packaging choices.